Transcatheter aortic valve replacement: the changing paradigm of aortic stenosis treatment. (September 2011) - Liff, David; Babaliaros, Vasilis; Block, Peter
Aortic stenosis is the most common cause for valvular surgery in the USA. For nearly 50 years, surgical aortic valve replacement has been the standard of care for symptomatic patients; unfortunately, a significant number of patients are not referred to surgery owing to advanced comorbidities and age. Transcatheter aortic valve replacement has emerged as an effective therapy for patients at high risk for surgery. Through device innovations and accumulated experience, the safety and efficacy of the procedure has improved since its inception. Transcatheter valve replacement has been found superior to medical therapy in inoperable patients with aortic stenosis, yet many questions remain as to which patients are appropriate for this exciting and novel therapy.